THE ROLE OF MULTICULTURAL SOCIETY IN MAINTENANCE OF POLITICAL STABILITY - Irina Aleksandrovna Rumachik (Современная наука и инновации)
Condition of political stability of the country are the steady, balanced relations between the people living on territories of the country. Political stability is reached including in multicultural society, by the optimization of the political and ethnic relations. At the same time the ethnic relations influence political processes. It is necessary for authorized institutes to find a constructive view to a role of multicultural society in maintenance of political stability.